Analisa Perbandingan Laju Pengeringan Biji Kakao Dengan Menggunakan Energi Listrik Dan Tenaga Surya - Romsin Hiras Naibaho; Jhon Sufriadi Purba; Winfrontstein Naibaho (Politeknik Negeri Padang, 2022)
Technological and economic developments are directly proportional to the industrial sector, especially in countries that are still developing. The food industry is one of them. Chocolate is one of the growing foods industri. The research on Comparison of the Drying Rate of Cocoa Beans Using a Dryer with Electricity and Solar Energy was carried out using an experimental method, namely with electricity coming from solar panels and then with electricity from PLN. The test aims to get a comparison of the effectiveness of electrical energy against solar panels. Cocoa beans that will be tested for drying before must be fermented first. The purpose of this test is to determine the drying time in a cocoa bean dryer with electricity and solar panels. This test uses the drying method using solar panels and uses electricity. Heat transfer in this test is conduction and convection. Test results are carried out in two stages. the first stage using electrical energy with the result of drying using cocoa beans weighing 2000 grams with a 271watt heater with the highest temperature of 43.6 0C can reduce the water content by around 59% from the mass of the 2000 gram sample weight of cocoa to 812 grams. The second stage is using solar panels where the drying process is divided into 2 stages, the first 8 hours with solar power and solar panels then the next stage using the help of batteries in the afternoon until evening. This stage can produce dry cocoa beans weighing 800 grams of dry cocoa beans from 2000 grams of wet cocoa beans. Thus, it can be concluded that the best drying using electric power can produce 812 grams of dry cocoa from 2000 grams of wet cocoa.